Homodyne and Heterodyne Terahertz Dielectric Sensors: Prototyping and Comparison in BiCMOS Technology for Lab-on-Chip Applications - Defu Wang; Klaus Schmalz; Mohamed H Eissa; Johannes Borngräber; Maciej Kucharski; Mohamed Elkhouly; Minsu Ko; Yong Wang; HJ (2018 IEEE International Microwave Biomedical Conference (IMBioC), 2018)
This paper for the first time prototypes and compares the homodyne and heterodyne terahertz dielectric sensors for lab-on-chip applications. The homodyne sensor consists of a multiplier chain, a balun-based power divider, an on-chip transducer, and IQ mixers. Differently, the heterodyne sensor requires an additional multiplier chain; however, it waives one mixer and a power divider, leading to reduced losses and alleviated power consumption. Fabricated using 0.13 µm SiGe BiCMOS technology, the homodyne and heterodyne sensors take 4 mm 2 and 5.2 mm 2 , and consume 400 mW and 499 mW, respectively. By experiments, both designed homodyne and heterodyne sensors can effectively sense the dielectric parameters of the samples. Moreover, the heterodyne sensor can address the DC offset issues with merely 99 mW additional power.